2002
DOI: 10.1074/jbc.c100614200
|View full text |Cite
|
Sign up to set email alerts
|

An mRNA Loop/Bulge in the Ferritin Iron-responsive Element Forms in Vivo and Was Detected by Radical Probing with Cu-1,10-phenantholine and Iron Regulatory Protein Footprinting

Abstract: Specific messenger RNA (mRNA) structures, identified in solution and exemplified by a set of noncoding mRNA regulatory elements (IRE) 1 and proteins (IRP) (1), control rates of protein synthesis (mRNA translation) or mRNA stability. The iso-IRE family, and the two related phosphorylatable regulatory proteins IRP1 and IRP2, are found in mRNAs encoding proteins of iron and oxygen homeostasis and constitute a natural set of combinatorial mRNA/protein interactions that give quantitatively different responses to ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…Several studies have shown that IRPs have different affinities for various IRE structures (34,35,48). IRP2 binds with greater affinity to the ferritin mRNA IRE than to the IREs of the TfR mRNA; this is attributed to the internal bulge found in the stem of the ferritin IRE (28,29). The crucial role of IRP2 in controlling ferritin levels in vivo also was indicated in recent studies demonstrating ferritin accumulation in the brains of IRP2 knockout mice (19).…”
Section: Discussionmentioning
confidence: 90%
“…Several studies have shown that IRPs have different affinities for various IRE structures (34,35,48). IRP2 binds with greater affinity to the ferritin mRNA IRE than to the IREs of the TfR mRNA; this is attributed to the internal bulge found in the stem of the ferritin IRE (28,29). The crucial role of IRP2 in controlling ferritin levels in vivo also was indicated in recent studies demonstrating ferritin accumulation in the brains of IRP2 knockout mice (19).…”
Section: Discussionmentioning
confidence: 90%
“…The site of Cu-(phen) 2 binding in the helix of the ferritin mRNA is the same site associated with metal binding, proton-induced disorder, and IRP2 binding in solution (17,32). Recent studies with HeLa cells confirm that the specific RNA fold of the ferritin IL/B, recognized by Cu-(phen) 2 , occurs in vivo as well (56). In the present study, using the wild-type TfR-3Ј-UTR RNA (5xIRE), Cu-(phen) 2 mediated the cleavage of nucleotides in the C-bulge region of TfR-IREc (Fig.…”
Section: Mtementioning
confidence: 82%
“…Chimeric RNAs between AMV and IRE, a proven PTL, were infectious to plants only when a transloop base pair at positions 1 and 5 of the hexanucleotide loop could form, indicating that the IRE PTL forms under in vivo circumstances. Recently, evidence for the structure of the ferritin IRE stem-loop in vivo was obtained by radical probing and protein footprinting in HeLa cells (26).…”
Section: Discussionmentioning
confidence: 99%